The use of yeast in food preparation in industry and agriculture and the development of independent forms of education in the teaching of the subject. (Conference Zone, 2022)
Microorganisms play an important role in our lives and are used effectively on an industrial scale, on a food scale and for a variety of purposes. This article provides information on the applications of microorganisms